A combinatorial approach to the elastic response of electrospun mats: Architectural framework and single fiber properties. (January 2023) - Singh, Danvendra; Sibal, Apurv; Sharma, Deepika; Sharma, Sumit; Sebők, Dániel; Satapathy, Bhabani K.; Goswami, Parikshit; Kukovecz, Akos; Rawal, Amit
Abstract: Electrospun is a unique class of porous and heterogeneous materials with multi-length-scales constituents that offer a rich variety of surface functionalities to serve a host of applications. Upscaling the electrospun materials from the laboratory to the industry is often limited by the lack of understanding of their mechanical properties. Herein, we developed a theoretical framework to predict the elastic constants of the electrospun mats that hinges on the concept of elastic properties of constituent fibers, three-dimensional (3D) alignment of fibers, and local fiber curvature. Enabled by continuum-based micromechanical approaches, this framework successfully predicted the elastic moduli regardless of bead-string morphology and local architectural heterogeneities present within the electrospun mats. The 3D fiber orientation distribution obtained using X-ray nano-computed tomography (nanoCT) analysis served as a key input for the validation of the analytical model. In general, the predicted elastic moduli are in reasonably good agreement with the experimental data of randomly oriented and preferentially aligned polylactic acid (PLA)-based electrospun mats. To demonstrate our analytical model's versatility and reliability, another set of PA6(3)-based electrospun mats has been chosen from the literature for validation purposes. The parametric analysis has been performed to provide a roadmap to improve the elastic moduli of electrospun mats and justify the assumed values of some of the key attributes. Graphical abstract: Image 1 Highlights: Elastic constants of the electrospun mats have been successfully predicted. Bead-string morphology and architectural heterogeneities present the challenges. Validated the model of elastic moduli with PLA and PA6(3)-based electrospun mats. Theoretical and experimental results are in reasonably good agreement. A roadmap to improve the elastic moduli of electrospun mats has been presented.